Livestock ecosystem services and disservices in a medium-sized South African town. Issue 1 (31st December 2022) - Thondhlana, Gladman; Yose, Papama; Cockburn, Jessica; Shackleton, Charlie
ABSTRACT: Production of livestock in urban spaces is a common phenomenon globally, particularly in the Global South. Livestock provides multiple benefits to society yet its production in urban spaces can result in adverse impacts to residents that can trigger conflicts. Understanding of the ecosystem services and disservices of livestock from the perspectives of residents can inform inclusive local management plans. Using household surveys and key informant interviews, this study sought to examine the contribution of livestock to owners, and perceptions of livestock services and disservices among non-livestock owners and key informants in Makhanda, a medium-sized South African town. Livestock owners derived multiple benefits from their livestock, including provisioning services such as meat, milk, skins and draught, and use livestock and livestock products in cultural activities such as rituals, bride price payments and funerals that are key elements of local identity. Among residents, there were marked differences in perceptions on the services and disservices of livestock which points to potential conflicts over urban land use and the need for addressing trade-offs. A key trade-off for local municipal authorities is addressing hunger and poverty by supporting well-regulated urban livestock production versus managing potential livestock disservices such as injuries to humans, livestock-vehicle collisions, health hazards and damage to urban green infrastructure. The trade-offs should be understood and considered by local authorities and residents as a basis for collectively developing strategies that can integrate livelihoods and cultural realities to balance competing demands for urban spaces including livestock production and other uses.